Sex transition from female to male as a risk factor for sleep-disordered breathing - Genzor, Samuel; Prasko, Jan; Mizera, Jan; Kufa, Jiri; Zurkova, Monika; Jakubec, Petr; Vykopal, Martin; Vanek, Jakub (Sleep medicine, 2023)
AIM: The female-to-male (FtM) sex transition requires lifelong supplementation with male sex hormones, resulting in high prevalence of weight gain, fat redistribution and other metabolic changes. Although sleep-disordered breathing (SDB) data for this group of patients are very limited, increased prevalence is expected. We report a mini-series of six case reports of FtM transsexuals treated in our centre. PATIENTS AND METHODS: All reported cases are consecutive patients referred to a department of respiratory diseases and tuberculosis of a university hospital from 2017 to 2022. The standard pulmonary examination was performed, followed by limited polysomnography. RESULTS: In all FtM subjects, SDB was present and continuous positive airway pressure (CPAP) therapy was indicated. The sex transition process was completed in three individuals while the other three only took testosterone supplementation at the assessment time. The subjects' age ranged from 21 to 38 years, the apnoea-hypopnea index ranged from 17.3 to 104.1, and the BMI was 33.48-43.41. The CPAP therapy was effective in five patients, with one requiring bi-level positive airway pressure therapy. One subject committed suicide before the first check-up, four patients had a good level of compliance at one-year follow-up, and one had insufficient CPAP adherence. CONCLUSION: SDB decreases the quality of life and life expectancy of FtM individuals. Their prognosis is undoubtedly better with effective treatment. Hence, obese FtM subjects should be considered at risk and screened for SDB.
Keywords: Sleep Apnea Syndromes; trvalý přetlak v dýchacích cestách; výsledek terapie; syndromy spánkové apnoe; mužské pohlaví; Adult; mladý dospělý; kvalita života; Young Adult; ženské pohlaví; Humans; Continuous Positive Airway Pressure; rizikové faktory; dospělí; Female; Quality of Life; Risk Factors; Treatment Outcome; lidé; Male